Does neutrophil-lymphocyte ratio show recurrence in patients who underwent curative resection for non-muscle-invasive bladder cancer? - Çelen, Sinan; Günseren, Kadir Ömür; Özlülerden, Yusuf; Mete, Aslı; Tuncay, Ömer Levent; Yavaşcaoğlu, İsmet (Journal of Surgery and Medicine, 2019)
Aim: The role of inflammation is a critical component of tumor progression and the neutrophil-lymphocyte ratio (NLR) reflects inflammatory status. We aimed to determine the clinical significance of the preoperative NLR in patients with non-muscle-invasive bladder cancer (NMIBC). Methods: A total of 178 patients, who underwent curative transurethral resection of bladder tumor (TURBT) for NMIBC between 2011 and 2016 in the urology department of Pamukkale University and Uludağ University were included in the study. Data including clinical characteristics, surgery, pathology, and follow-up were obtained from a retrospectively maintained database. Patients were divided into groups according to pre-operative NLR values (h-NLR group: ≥2.5, l-NLR group: NLR <2.5). Their cut-off values were determined through receiver operation characteristics curves analysis. Recurrence rates of the patients were determined in the 1st year follow-up. For further analysis, all of the patients were allocated according to their risk ratio according to European Organization for Research and Treatment of Cancer (EORTC) tables as low, intermediate and high, and all of the groups have been evaluated according to the risk ratio. Results: NLR patients (55.6% of the cases) were associated with worse risk of bladder cancer recurrence as compared to l-NLR group (P=0.005). Kaplan-Meier plots illustrated that higher pre-operative NLR had decreased disease-free survival (DFS). Low pre-operative PLR and NLR levels correlated with recurrence. Conclusion: The present research shows that NLR is a prognostic indicator in NMIBC. Calculating NLR value might be useful at predicting recurrence in NMIBC patients.